Eva1a ameliorates atherosclerosis by promoting re-endothelialization of injured arteries via Rac1/Cdc42/Arpc1b. Issue 2 (24th January 2020) - Li, Jingxuan; Chen, Yingyu; Gao, Jianing; Chen, Yue; Zhou, Changping; Lin, Xin; Liu, Changjie; Zhao, Mingming; Xu, Yangkai; Ji, Liang; Jiang, Zongzhe; Pan, Bing; et al.
Abstract: Aims: Eva-1 homologue 1 (Eva1a) is a novel protein involved in the regulation of cardiac remodelling and plaque stability, but little is known about its role in re-endothelialization and the development of atherosclerosis (AS). Thus, in the present study, we aimed to elucidate the function of Eva1a in re-endothelialization and AS. Methods and results: Wire injuries of carotid and femoral arteries were established in Eva1a −/− mice. Eva1a -deficient mice were crossed with apolipoprotein E −/− (ApoE −/− ) mice to evaluate AS development and re-endothelialization of carotid artery injuries. Denudation of the carotid artery at 3, 5, and 7 days was significantly aggravated in Eva1a −/− mice. The neointima of the femoral artery at 14 and 28 days was consequently exacerbated in Eva1a −/− mice. The area of atherosclerotic lesions was increased in Eva1a −/− ApoE −/− mice. To explore the underlying mechanisms, we performed transwell, scratch migration, cell counting kit-8, and bromodeoxyuridine assays using cultured human aorta endothelial cells (HAECs), which demonstrated that EVA1A promoted HAEC migration and proliferation. Proteomics revealed that the level of actin-related protein 2/3 complex subunit 1B (Arpc1b) was decreased, while Eva1a expression was absent. Arpc1b was found to be a downstream molecule of EVA1A by small interfering RNA transfection assay. Activation of Rac1 and Cdc42 GTPases was also regulated by EVA1A. Conclusion: This study provides insights into anti-atherogenesis effects of Eva1a by promoting endothelium repair. Thus, Eva1a is a promising therapeutic target for AS.